The ash girl - Wertenbaker, Timberlake (Faber and Faber, 2000)
With her mother dead and her father away, the Ash Girl lives huddled deep in the protection of the ashes with her stepmother and two stepsisters. When an invitation to the Ball, addressed to all the daughters of the house, arrives from Prince Amir, Ashie can't believe that she can go too.